Structured computer organization - Tanenbaum, Andrew S., 1944- (Upper Saddle River : Pearson, 2006)
Specifically written for undergraduate students, this best-selling guide provides an accessible introduction to computer hardware and architecture. Updated content is delivered via the familiar structure that has served instructors through four successful editions, with the major addition of an accompanying assembly language instructional CD-ROM.
Keywords: Computerarchitectuur